Osteocalcin—A Versatile Bone-Derived Hormone - Moser, Sarah C.; van der Eerden, Bram C. J. (Frontiers in Endocrinology, 2019)
Bone has long been regarded as a static organ, simply providing protection and support. However, this mindset has changed radically in recent years and bone is becoming increasingly recognized for its endocrine function of secreting several hormones and thereby controlling various physiological pathways. One of the factors released by the skeleton is osteocalcin. Importantly, osteocalcin is solely secreted by osteoblasts but only has minor effects on bone mineralization and density. Instead, it has been reported to control several physiological processes in an endocrine manner, such as glucose homeostasis and exercise capacity, brain development, cognition and male fertility. The aim of this review is to provide an overview of the currently known roles of osteocalcin and their underlying mechanisms. At present, one of the major goals in this field is translating basic research into therapeutic applications, therefore ongoing efforts to bring these findings to the clinics will also be discussed.